2020
DOI: 10.37398/jsr.2020.640117
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Uses of Traditionally Used Plants in Bhatwari Block, District Uttarkashi, Uttarakhand, India

Abstract: The prolific plant diversity of Uttarakhand hills has provided an initial lead to the local people to look for various plant species for the purpose of food, medicine, spices and perfumes. Over the period of time, they have compiled the knowledge on the use of various plant species. The present study aims to document such information, especially the use of plants for medicine, as spice and as perfumes. Field surveys carried out in the villages of Bhatwari block have resulted in the documentation of 60medicinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Aconitum lethale was used to treat, snake bite, scorpion sting, boils, gout and rheumatism, similar to Singh et al 2019, while Bisht & Badoni, (2009 reported it for joint pain. Nardostachys jatamansi was used to treat epilepsy, mental disorders, insomnia, and heart diseases similar to (Kunwar et al 2009, Singh et al 2017, Tamang et al 2021, Monika et al 2020) however, Kunwar et al (2009) reported that the oil of Nardostachys jatamansi is used for headaches. Solanum nigrum was used for the treatment of fever, indigestion, coolant, headache, cuts and wounds similar to (Singh et al 2017, Kumari et al 2021, Gaur and Sharma 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aconitum lethale was used to treat, snake bite, scorpion sting, boils, gout and rheumatism, similar to Singh et al 2019, while Bisht & Badoni, (2009 reported it for joint pain. Nardostachys jatamansi was used to treat epilepsy, mental disorders, insomnia, and heart diseases similar to (Kunwar et al 2009, Singh et al 2017, Tamang et al 2021, Monika et al 2020) however, Kunwar et al (2009) reported that the oil of Nardostachys jatamansi is used for headaches. Solanum nigrum was used for the treatment of fever, indigestion, coolant, headache, cuts and wounds similar to (Singh et al 2017, Kumari et al 2021, Gaur and Sharma 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Picrorhiza kurrooa is used against fever, abdominal pain, coolant and intestinal worms. Singh et al (2019), Malik et al (2015), Singh & Rawat (2011), Kunwar et al (2009) reported it for fever and stomachache, Masood et al (2015) reported to cure stomachache and high fever, while Monika et al (2020) reported it for biliousness, urinary discharge, blood troubles, burning sensations, leukoderma, and jaundice, while Rana et al (2019) reported it for fever and jaundice, Ahmad et al (2014) digestive complaints, heart disease. Saussurea obvallata is used for the treatment of asthma however, Kirtikar & Basu 1984,Monika et al (2020 reported to cure cardiac diseases, cuts and wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al (2020) reported that the one of the most famous tradition Chinese medicinal herb Abrus cantoniensis Hance (AC) is used to cure hepatitis B virus (HBV) by inhibiting the production of HBV DNA as well as Hepatitis Be Antigen (HBsAg), and Hepatitis B surface antigen (HBsAg). From India (Monika et al 2020) also showed that some medicinal plants i.e. the leaf and flower part of the Pandanus fascicularis Lam, the root of the Berberis aristata DC and the whole plant of Oxalis corniculata L is used for the treatment of hepatitis.…”
Section: Family Importance Valuementioning
confidence: 99%
“…Human culture has been fascinated by medicinal plants since prehistoric times. India has a diverse range of medicinal plants at all three levels of biodiversity: species, genetic diversity, and habitat diversity 1 . The Himalayas are well-known for having some of the world's most diverse biodiversity hotspots 2 .…”
Section: Introduction Uttarakhand's Medicinal Plantsmentioning
confidence: 99%